Do Bank-Based Financial Systems Reduce Macroeconomic Volatility by Smoothing Interest Rates? - Johann Scharler (Oesterreichische Nationalbank (OeNB), 2006)
This paper investigates the business cycle implications of limited pass-through to retail interest rates based on a calibrated sticky price model. Although limited interest rate pass-through can in principle reduce output and inflation volatility at the same time, large reductions in output volatility are likely to be accompanied by a more volatile inflation rate. Limited pass-through gives rise to two counteracting effects: It partially insulates the economy from adverse liquidity shocks and thereby leads to lower output volatility. However, it also reduces the stabilizing effect of monetary policy which implies higher inflation volatility.
Keywords: E32; E44; E52; 330; Financial Systems; Interest Rate Pass-Through; Business Cycle